Modelling Product and Partners Network Architectures to Identify Hidden Dependencies - Zouggar, S.; Zolghadri, M.; Girard, P. (Cranfield University Press, 2009)
This paper explores mutual dependencies between partners of a New Product Design (NPD) project during the realization phase. It highlights bidirectional influences between components and partners. Linking product and network architectures is achieved through gBOMO (generalised Bill Of Materials and Operations) that allows expressing product components use and partners interventions in the network. We develop an approach to achieve building Dependency strength matrix. Analysing this matrix reveals obvious and hidden dependencies between partners which should be anticipated in early stages of the NPD project. The approach is illustrated through its application on an engine.
Organised by: Cranfield University
Keywords: Partners network; Product architecture; Logical dependencies; NPD project